Analysis Of Factors Affecting Individual Taxpayers In Fulfilling The Obligation To Pay Taxes - IRAWAN, Ari; SEBAYANG, Minda (International Journal of Environmental, Sustainability, and Social Science, 2021)
The purpose of this study was to determine the variables that influence the willingness to pay taxes, namely awareness of paying taxes, knowledge and understanding of tax regulations, good perceptions of the tax system, and quality of service to taxpayers. The method used in this research is convenience sampling method. The conclusion in this study is that the variable awareness of paying taxes, knowledge and understanding of tax regulations, a good perception of the tax system, and the quality of service to taxpayers have a positive and significant influence on willingness to pay taxes at KPP Pratama Medan Belawan. taxes, knowledge and understanding of tax regulations, a good perception of the tax system, and the quality of service to taxpayers by 40.9% and the remaining 59.1% is influenced by other factors not examined in this study.